PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN PUPUK CAIR AB MIX TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annum L.) DI POLIBAG - Pahala L. L. Sianturi; Chichi Josephine Florestina Manalu; Eben Ezer Marpaung (Majalah Ilmiah METHODA, 2021)
The need for red chilies continues to increase. Therefore, it is necessary to increase production through improved cultivation techniques, including fertilization. For this reason, research is needed to determine the effect of concentration and time interval of giving AB mix liquid fertilizer on the growth and production of red chili plants (Capsicum annum L). This research was conducted at Jalan Tinta, Ayahanda, Medan Petisah District, Medan, North Sumatra with a height of ± 25 meters above sea level, which was conducted in May - August 2020. This study used a factorial randomized block design (RBD) with 2 factors. The first factor is the nutrition of AB mix (N) which consists of 3 levels, namely: N1 = 1000 ppm, N2 = 1250 ppm and N3 = 1500 ppm. The second factor is the time of giving AB mix nutrition (W) consisting of 3 levels, namely: W1 = 1 x 2 days, W2 = 1 x 4 days and W3 = 1 x 6 days. The results showed that the treatment of 1500 ppm AB Mix nutrient concentration had a significant effect on plant height at the age of 56 HST, but had no significant effect on flowering age, number of fruits per plant, fruit diameter, fruit length, weight per fruit, fruit weight per plant and weight. pieces per plot. The time interval for AB Mix nutrition gave significant effect on the number of fruits per plant, fruit weight per plant and fruit weight per plot, but had no significant effect on plant height, flowering age, fruit diameter, fruit length and weight per fruit of red chilies. The interaction between concentration and time interval of AB Mix nutrition had no significant effect on plant height, flowering age, number of fruits per plant, fruit diameter, fruit length, fruit weight per plant and fruit weight per red chili plant plot.